Quality of life for parents of children with type 1 diabetes - Mir Rashidi, Fatemeh Sadat; Korki Nejat, Fatemeh; Rezaiye, Milad; Gholami, Mohammad Hossein; Rezabeigi Davarani, Esmat; Daneshi, Salman; Kiani, Amin; Ghorbani Aliabadi, Elham; Sheikh Beig Goharrizi, Mohammad Ali; Gholamrezaie, HamidReza (Archives of Advances in Biosciences, 2021)
Introduction: Parents whose children suffer from diabetes face various issues and challenges, including reduced quality of life. On the other hand, they have an essential role in taking care of their diabetic children. Material and method: This descriptive correlational study was conducted in 2020 in Jiroft, Iran, to evaluate the quality of life in 96 parents of children with type 1 diabetes. The sampling method in this study was census and the study population was parents with a child suffering from type 1 diabetes. Research tools included Demographic Information Checklist and Health-related quality of life Questionnaire (SF36). SPSS 19 software was used for data analysis. Descriptive statistics was used as frequency tables, and indicators such as mean and standard deviation described the demographic characteristics and the quality of life. Pearson correlation coefficient test was deployed to assess the quality of life. Independent chi-square and t-test were used to relate this variable to demographic characteristics. Results: There is a significant difference between life satisfaction, parental boredom, feeling of well-being, sufficient income, general health status, and being covered by supportive institutions of parents of type 1 diabetic children with the quality of life (p-value <0.05). Conclusion: By knowing this group of parents' living conditions and implementing programs to support these families, the quality of life of parents with a diabetic child can be improved.